The Preprints and Discussions for Brazilian Nursing (Research, Society and Development, 2022)
Objective: Identify the main reflections in the context of preprints in the area of nursing and, secondly, to Discuss the relevance of preprints to Brazilian science from the perspective of nursing. Methodology: qualitative research through an integrative literature review, on the theme of relevance of preprints from the perspective of Brazilian nursing. Six studies were analyzed, of which (2) were indexed to MEDLINE, (2) SciELO, (1) LILACS and (1) PUBMED. Results: It was verified that until the year 2018, preprints did not occur frequently in nursing publications, however, their use in academic publications belongs to a common practice in several disciplines. Accessibility and impact advantages were identified, since research results are freely accessible to all who are interested, unlike many journals, whose subscription or acquisition of articles is expensive. Conclusion: There has been a high increase in productions in the form of preprints in the area of public health in recent years. The use of the preprint publication model is expanding in the area of nursing and its use does not occur with the same frequency as in other fields such as physics, chemistry and mathematics.